Subcellular localization of p44/WDR77 determines proliferation and differentiation of prostate epithelial cells. - Shen Gao (Public Library of Science (PLoS), 2012)
The molecular mechanism that controls the proliferation and differentiation of prostate epithelial cells is currently unknown. We previously identified a 44-kDa protein (p44/wdr77) as an androgen receptor-interacting protein that regulates a set of androgen receptor target genes in prostate epithelial cells and prostate cancer. In this study, we found that p44 localizes in the cytoplasm of prostate epithelial cells at the early stage of prostate development when cells are proliferating, and its nuclear translocation is associated with cellular and functional differentiation in adult prostate tissue. We further demonstrated that cytoplasmic p44 protein is essential for proliferation of prostate epithelial cells, whereas nuclear p44 is required for cell differentiation and prostate- specific protein secretion. These studies suggest a novel mechanism by which proliferation and differentiation of prostate epithelial cells are controlled by p44's location in the cell.